Pattern recognition as a new strategy in high-resolution spectroscopy: application to methanol OH-stretch overtones. Issue 36 (2nd September 2021) - Rakovský, Jozef; Svoboda, Vít; Horká-Zelenková, Veronika; Votava, Ondrej
Abstract : We develop an approach for line-by-line assignments of complex high-resolution overtone spectra based on ground state combination differences. Observed line patterns in the spectra determine energies and rotational assignments of individual upper ro-vibrational levels. Abstract : We further develop a strategy for a line-by-line assignment of complex high-resolution overtone spectra. A search for specific line patterns in the spectrum allows to identify upper rotational states by extending the concept of ground state combination differences (GSCD). Simultaneous use of all GSCDs relating to a given upper state significantly reduces a probability of incorrect assignments. To test this approach, we have analysed a newly recorded spectrum of methanol in the first OH-stretch overtone region, 2 ν OH, between 7170 cm −1 and 7220 cm −1 at temperature of 19 K by combining a tunable-laser-diode absorption spectrometer with a slit-jet supersonic expansion. The spectrum consists of 1002 lines at this low temperature reflecting the fact that methanol is an asymmetric rotor with a hindered internal rotation. In total, 295 lines have been reliably assigned, representing 63% of the total intensity. Rotational energies and rotational quantum numbers for 52 upper states have been determined. Many of these states have the same quantum numbers, suggesting couplings to a manifold of 'dark' vibrational states in this overtone region.